2015
DOI: 10.1007/s11064-015-1594-1
|View full text |Cite
|
Sign up to set email alerts
|

Brain Glycogen Decreases During Intense Exercise Without Hypoglycemia: The Possible Involvement of Serotonin

Abstract: Brain glycogen stored in astrocytes, a source of lactate as a neuronal energy source, decreases during prolonged exercise with hypoglycemia. However, brain glycogen dynamics during exercise without hypoglycemia remain unknown. Since intense exercise increases brain noradrenaline and serotonin as known inducers for brain glycogenolysis, we hypothesized that brain glycogen decreases with intense exercise not accompanied by hypoglycemia. To test this hypothesis, we employed a well-established acute intense exerci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…In the present study, mice submitted to exercise showed higher levels of serotonin turnover. This is in agreement with a previous report showing an improvement of depressive symptoms and high striatal serotonin turnover after aerobic exercise [17,46]. Clinical study shows that unmedicated patients with major depression show higher serotonin turnover levels [47].…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, mice submitted to exercise showed higher levels of serotonin turnover. This is in agreement with a previous report showing an improvement of depressive symptoms and high striatal serotonin turnover after aerobic exercise [17,46]. Clinical study shows that unmedicated patients with major depression show higher serotonin turnover levels [47].…”
Section: Discussionsupporting
confidence: 92%
“…In the latter group, however, lactate levels were already elevated at baseline and remained consistently high during the visual stimulation [ 20 ]. Besides its role as energy substrate of the brain, lactate acts as a neuromodulator and interacts with glutamate [ 21 ], GABA [ 22 ], and monoamines [ 23 ], which suggest that it is important in regulating the activity of cortical neurons. Lactate may increase to attenuate the electrical activity of excessively active neurons as observed in experimental models [ 22 , 24 , 25 ] and in healthy humans during sustained visual stimulation [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Takashi et al suggested that serotonin (5-HT) turnover increased in the hippocampus and brainstem and was associated with a decrease in glycogen. As a result, they concluded that serotonergic neurons in the hippocampus and brainstem are likely to regulate the intense exercise-induced brain glycogenolysis [29].…”
Section: Exercise Triggered Haaf and Solutionsmentioning
confidence: 99%